Learning in Myanmar : Pre and Post-Covid-19 - World Bank (Washington, DC : World Bank, 2022)
This brief summarizes the state of student learning outcomes in Myanmar before the onset of the COVID-19 pandemic, and presents retrospective estimates of the losses in learning and future earnings of students resulting from the disruptions caused by the pandemic and the military coup of February 1, 2021. It shows that Myanmar had been facing a learning crisis even before the COVID-19 pandemic as reflected in very low levels of learning outcomes in reading and math, and large disparities in learning outcomes across different population groups. This crisis was aggravated by the pandemic and the coup which caused schools to remain closed for almost two years. As a result, the children in Myanmar have been experiencing significant learning losses which will, in turn, also reduce their future earnings substantially. This points to the need for both shorter term learning recovery focused interventions as well as longer term interventions aimed at strengthening system resilience.